Futuristični aeroples in Giannina Censi - Lipoglavšek, Manca (Amfiteater (Ljubljana), 2025)
This article discusses the development of Futurist dance and Giannina Censi’s role as a key figure in this artistic form. As an artistic movement, Futurism rejected traditional aesthetics, particularly ballet and classical dance, and sought a radical reinvention of dance’s means of expression. The central ideas of Futurist dance were based on denying gracefulness, beauty and symmetry, while celebrating machines, technology, speed and aggression. The concurrent development of modern and contemporary dance introduced freedom, the liberation of the body and rebellion against social norms into the artistic realm, enabling women to emerge as autonomous performers and creators. Pioneers such as Isadora Duncan, Loie Fuller and others emphasised subjectivity, self-confidence and feminist elements through their innovations in dance. These two influences merged in dancer Giannina Censi, who represented a unique figure in the field of Futurist dance through her collaboration with F. T. Marinetti and by directly realising his vision, thereby creating the concept of aerodance or aerodanza. Her dance was based on mechanical gestures, expressing the mechanical quality of machines while also containing erotic elements and emphasising the female body as the carrier of futuristic technology. Through her artistic expression, she rejected the male Futurist ideal and introduced her own female subjectivity, marking an important departure from traditional, ideologically sanitised forms of Futurist dance.
Keywords: avantgardna gibanja; Censu, Giannina; futuristična tehnologija; futuristični ples; futurizem; moderni ples; spol; umetniška ekspresija; ženske